Instrumental delivery: a comparative study in a tertiary care hospital - B. T., Bhanu; G. S., Anitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: To compare maternal and neonatal outcomes of vacuum versus forceps application in assisted vaginal delivery. Methods: Women in labor with vertex presentation were delivered by indicated/propylactic vacuum or forceps. A total of 500 cases were included in this retrospective study. Maternal and neonatal morbidity were compared in terms of perineal lacerations, episiotomy extension, post-partum hemorrhage, Apgar score, neonatal jaundice, perinatal mortality, NICU admissions etc. Chi square test was used to analyze the data. Results: Maternal morbidity was significant in the forceps group. With regards to neonatal morbidity, in NICU admissions, statistically significant difference was noted. Conclusions: Vacuum and forceps should remain appropriate tools in the modern obstetrics. However, ventouse may be chosen first (if there is no fetal distress) as it is significantly less likely to injure the mother and decrease NICU admissions.